The feasibility of assessing speech and non-speech function of the speech apparatus in adults with cerebral palsy. (2nd September 2018) - Schölderle, Theresa; Staiger, Anja; Ziegler, Wolfram
ABSTRACT: This short note reports on observations concerning the feasibility of a set of speech and non-speech assessment tasks in an investigation of dysarthria in 21 adults (15 males/6 females; median 23 years) with cerebral palsy and concomitant cognitive impairment. The participants were assessed with nine tasks representing standard components of clinical dysarthria assessment (i.e. six speech and three non-speech tasks). The tasks were evaluated for their feasibility on the basis of common clinical criteria. Our results indicated that, overall, speech tasks were more feasible than non-speech tasks. Several participants showed signs of dysexecutive behaviour on some of the non-speech tasks, but not on the speech tasks. The current note provides tentative clues regarding the impact of cognitive deficits on the feasibility of assessment tasks in the diagnosis of dysarthria.